Strategi Humas Direktorat Jenderal Pajak Kantor Wilayah Jawa Timur 1 dalam Meningkatkan Kepatuhan Pembayaran Pajak Tahunan - Qozi, Iqbal Zukhrufal; Tatak Setiadi (The Commercium, 2025)
Taxes is important role in the Indonesian economy and are the main source of state income. The Directorate General of Taxes East Java Regional Office 1 in Surabaya is responsible for ensuring taxpayer compliance. The government has made various efforts to improve taxpayer compliance. With public relations role, DGT educates the public, strengthens relationships with the community, and enhances its positive image to achieve annual tax targets. The observation is intended to identify the public relations strategy of DGT East Java Regional Office 1 in improving annual tax compliance. This observation employs a qualitative descriptive methods with a case study approach. Observers collect data through structured interviews and documentation. The results show that the public relations strategy of DGT East Java Regional Office 1 is effective in improving annual tax compliance. The survey shows that the effectiveness of public relations varies, with the highest peak in 2024 (97.25%) following a decline in 2023. Through the use of social media, education, tax “Kring”, public relations have successfully built a positive image and increased tax awareness in the community.